Pemidanaan Terhadap Pekerja Seks Komersial Melalui Aplikasi Michat The Liability of Prostitute On Michat - Putu Eva Ditayani Antari (Program Studi Ilmu Hukum Universitas Maritim Raja Ali Haji, 2022)
In this pandemic era, technology is an alternative way to do activities to facilitate human activity. The legal aspects that regulate life which aim to regulate harmonization between humans are often violated by certain elements to gain profits, apart from globalization. Prostitution is also involved because online media, the many elements who promote prostitution in the Michat online application are the main attraction for the audience, as a result of this prostitution many violate social norms that exist in society and become a problem. The problem that the author will analyse is what are the sanctions for perpetrators of online prostitution through the Michat application and the efforts that can be made to prevent the rise of online prostitution in Indonesia. The research method used is normative legal research with data collection techniques through library research. The results of the research obtained are first, pimps can be charged with the threat of punishment, both imprisonment and fines, the prohibition of doing pimping professions is contained in article 296 and article 506 of the Criminal Code. Regulations regarding the prohibition of online prostitution are specifically regulated in Article 27 paragraph (1) of Law Number 11 of 2008 concerning Information and Electronic Transactions. Second, preventive prevention of prostitution is carried out by various parties, both from government agencies and the local community so that it can run smoothly. maximum. The Regional Head, DPRD, Satpol PP, and the Police need to work together with the community to take the actions described above to prevent the practice of prostitution in their area.